Tuning Optical Properties and Photocatalytic Activities of Carbon‐based "Quantum Dots" Through their Surface Groups. Issue 1 (12th December 2015) - Hu, Shengliang
Abstract: We report recent progress in tuning optical properties and photocatalytic activities of carbon‐based quantum dots (carbon‐based QDs) through their surface groups. It is increasingly clear that the properties of carbon‐based QDs are more dependent on their surface groups than on their size. The present challenge remains as to how to control the type, number, and conformation of the heterogeneous groups on the surface of carbon‐based QDs when considering their target applications. By reviewing the related achievements, this personal account aims to help us understand the roles different surface groups play in tuning the properties of carbon‐based QDs. A number of significant accomplishments have demonstrated that surface groups possess strong power in engineering electronic structure and controlling photogenerated charge behaviors of carbon‐based QDs. However, effective strategies for modifying carbon‐based QDs with diverse heterogeneous groups are still needed. Abstract : Surface group regulation for tuning properties of carbon‐based "quantum dots" : The photophysical and photochemical properties of carbon and graphene quantum dots are more dependent on their surface groups than on their size. Different heterogeneous groups play different roles in engineering electronic structure and controlling photogenerated charge behaviors of these quantum dots.